Use of multikinase inhibitors/lenvatinib in patients with synchronous/metachronous cancers coinciding with radioactive‐resistant differentiated thyroid cancer. (6th October 2022) - Sambo, Marcel
Abstract: This review focuses on patients with differentiated thyroid carcinoma (DTC) associated with multiple primary malignant neoplasm (MPMN) treated by multikinase inhibitors (MKIs) as systemic treatment for advanced disease. Despite the increasing frequency of MPMNs (many at an advanced stage) and the usefulness of MKIs for multiple metastatic cancers, published data on the management of MPMN and MKI therapies in this scenario are scarce. There are infrequent descriptions of patients with advanced MPMN treated with MKIs, but only a few have described advanced DTC. The management of MPMNs, including DTC and its particular circumstances, is reviewed, focusing on the evidence for MKI therapies. Some considerations for MPMN patients with advanced DTC are discussed, with the intention of helping physicians make decisions in these challenging situations and improving treatment and patient outcomes. Abstract : Although the frequency of multiple primary malignant neoplasms (MPMNs) is increasing, published data on the management of MPMNs with multikinase therapies are scarce, particularly for advanced differentiated thyroid carcinoma (DTC). This article reviews the management of MPMNs, including considerations for MPMN patients with advanced DTC.